Response of phytoplankton biomass to nutrient stoichiometry in coastal waters of the western Bay of Bengal. (November 2021) - Mathew, Teesha; Prakash, Satya; Kumar Baliarsingh, Sanjiba; Samanta, Alakes; Lakshmi, R.S.; Anandrao Lotliker, Aneesh; Chatterjee, Abhisek; Balakrishnan Nair, T.M.
Highlights: Prominent seasonality in spatial variation of hydro-biological parameters. Cold-core eddy fuelled higher pre-southwest monsoon chlorophyll- a levels. Lower surface chlorophyll- a levels despite higher nutrient during post-southwest monsoon. Potential role of nutrient stoichiometry in determining chlorophyll- a seasonality. Post-southwest monsoon phosphate-limitation induced lower chlorophyll- a levels off Godavari. Abstract: The hydro-biological parameters such as thermohaline structure, nutrients, and chlorophyll- a (chl- a ) during pre-southwest monsoon (PRSWM) and post-southwest monsoon (POSWM) periods of 2017, was investigated and compared along a coastal transect in the western Bay of Bengal (BoB). The impact of cold-core and warm-core eddies on chl- a in the very near coastal waters of the western BoB was analyzed. During PRSWM period, the water column was recharged with phytoplankton growth-promoting nutrients entrained by cold-core eddies that resulted in an increment in chl- a concentration. A three-times increase in chl- a concentration was observed due to the cold-core eddy, whereas the presence of warm-core eddy reduced the chl- a concentration by 87%. However, during POSWM period, despite having higher nitrate concentration and adequate light in the water column, the surface chl- a was substantially lesser than PRSWM. The molar ratio of ambient inorganic macronutrients during POSWM period played a significant role resulting in lower chl- a concentration. Nitrogen to phosphate (N:P) and nitrogen to silicate (N:Si) ratios were less than the Redfield values. The chl- a concentration off Godavari, a biological hotspot, was the lowest during POSWM period. This study highlights phosphate limitation off Godavari during the high river discharge period.